Updated description of the Dicynodontipus- and Chirotherium- bearing slab from the Solling Formation, Hildburghausen town, Germany - de Valais, Silvina (2020)
A track-bearing slab (MNHN.F.AC10007) from the Solling Formation of Hessberg (Hildburghausen, Thuringia, central Germany) is housed in the Muséum national d´Histoire naturelle of Paris, France, since 1835. The Solling Formation, Olenekian–Anisian in age, pertains to the lowermost part of the Germanic Triassic and records the evolution braided to sinuous meandering channels. Foot-- nally, the slab was about 2.21 m long and 1.56 m maximum width, while nowadays the maximum wide is 1.36 m, seeing that a portion has been lost. On the slab, four vertebrate trackways are preserved as concave epirelief and interfered with polygonal cracks, likely testifying a desiccation event. One trackway, holotype of Dicynodontipus hildburghausensis Rühle von Lilienstern, 1944, is composed of six manus-pes sets, plus a further set in the lost portion. The rest of the footprints are assigned to the ichnogenus Chirotherium Kaup, 1835. Chirotherium barthii Kaup, 1835, is represented by a trackway composed of six manus-pes sets preserving skin impressions, while a trackway of two manus-pes sets and a footprint, with a fourth set in the lost area, is referred to as Chirotherium sickleri Kaup, 1835. Finally, a trackway composed of three manus-pes sets, not idenwith Chirotherium, although ichnotaxonomical assignment is to date prevented. Further up-todate studies are currently underway, including 3D photogrammetric models, to provide a thorough re-discussion of the trackways, as well as their ichnotaxonomical and palaeobiological significance.